Outcome of Active versus Expectant Management in Preterm Premature Rupture of Membranes between 34 weeks to 36 weeks Six days: A Retrospective Study - Shilpaann Baby; M Anjali (Journal of Clinical and Diagnostic Research, 2022)
Introduction: An important cause of neonatal morbidity and mortality is the prelabour Preterm Rupture of the Membranes (PPROM) which refers to, the rupture of the membranes before 37 weeks. There are two modes of managing PPROM, active management (immediate delivery) and expectant management (therapy directed toward extending the pregnancy to improve neonatal outcome). Aim: To compare neonatal outcomes following active and expectant (conservative) management in PPROM cases from 34 weeks to 36 weeks six days. Materials and Methods: This retrospective study was conducted in the Department of Obstetrics and Gynaecology at Government Medical College (tertiary care teaching hospital), Thiruvananthapuram Kerala, India, from February 2021 to July 2021. The data collection period was from January 2013 to December 2014. PPROM cases between 34 weeks and 36 weeks and six days were retrospectively studied. A total of 62 patients among the Active Management (AM) group and 62 patients among the Expected Management (EM) group were selected. The neonatal outcomes (respiratory distress syndrome, hypoglycaemia, neonatal sepsis) and maternal outcomes (caesarean section, chorioamnionitis) were compared. The latency period in conservative management and in active management was also compared. The data was analysed using the Chi-square test. Results: In the AM group, 13 (21%) babies had respiratory distress syndrome, whereas, in the EM group it was 4 (6.5%) (p-value=0.019). In the AM group, 13 (21%) babies had hypoglycaemia, whereas, in the EM group, it was 5 (8.1%) (p-value=0.041). In the AM group, 3 (4.8%) women had signs and symptoms of chorioamnionitis, whereas, in the EM group, it was 7 (11.3%) (p-value=0.187). In the AM group, 16 (25.8%) of women had Caesarean section, whereas, in EM it was 9 (14.5%) (p-value=0.117). In AM group, 1 (1.6%) has neonatal sepsis and in EM it was 3 (4.8%) p-value=0.309. The latency period in conservative management was 119.5±31 hours and in active management, it was 51.5±13.2 hours. Conclusion: The present study indicated that expectant management of PROM between 34 weeks to 36 weeks and six days leads to a statistically significant reduction of neonatal respiratory distress syndrome and hypoglycaemia.